The persistence of the collective: A comparative approach to images of the trade union body in 1963 and 2017 in Argentina - Bauso Beltrán, Federico (Re-visiones, 2024)
The present article offers a comparative approach to images that depict the trade union body, in 1963 and 2017. The aim is to highlight the continuities and changes in the shaping of this masculine and organised corporality, in two images from the 1960s and the 2010s, to ascertain how this social body of the union is outlined in these distinct periods. As such, we propose to study the 1963 poster ¡Basta! (“Enough!”) by the visual artist Ricardo Carpani (1930-1997) and the untitled 2017 photograph by Fernando de la Orden (1976-), taken for the newspaper Clarín.
Keywords: Worker’s body; trade unions; resistance; workers; image